2012
DOI: 10.1248/cpb.60.195
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Novel and Diverse 16-Norphragmalin-Type Limonoids from Chukrasia tabularis var. velutina

Abstract: A series of novel and structurally related C-15-acyl 16-norphragmalin-type limonoids, chuktabrins C-J (1-8) and chuktabularins U-X (9-12), were isolated from the stem bark of Chukrasia tabularis var. velutina. Their structures were established on the basis of detailed spectroscopic analysis, and the absolute configuration of compound 1 was determined by a single-crystal X-ray study using a mirror CuKα radiation. Compounds 7 and 8 were unprecedent C-15-acyl 16-norphragmalins with ketonic alkyl appendage at C-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Thus, these correlation required the presence of -OR substituent at C-8, C-9 and C-30. The 13 C-NMR data for C-30, C-9 and C-8 were similar to those for chuktabrin C, which was determined by single-crystal X-ray diffraction [ 8 ], determining the position of enol ether at C-30 and the carbonate moiety at C-8 and C-9.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Thus, these correlation required the presence of -OR substituent at C-8, C-9 and C-30. The 13 C-NMR data for C-30, C-9 and C-8 were similar to those for chuktabrin C, which was determined by single-crystal X-ray diffraction [ 8 ], determining the position of enol ether at C-30 and the carbonate moiety at C-8 and C-9.…”
Section: Resultsmentioning
confidence: 63%
“…The key ROESY correlations ( Figure 3 ), from H-5 to H-11, H-17, and H-21, H-17 to H-5, H-11, H-21, and H-30, Me-18 with H-14 and H-22, H-29a with H-3, and H-29b with H-19b, indicated that the relative stereochemistry of the key asymmetric carbons of 1 was well matched with those of chuktabrin C obtained by X-ray crystallography [ 8 ]. Thus, the structure of 1 was established as shown in Figure 1 , namely as a 12-deacetyl derivate of chuktabrin H [ 8 ].…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations